Information for global mental health. (19th August 2015) - Lora, A.; Sharan, P.
Abstract : Background: Information is needed for development of mental health (MH) services; and particularly in low- and middle-income countries (LAMICs), where the MH systems are relatively weak. World Health Organization (WHO) has worked intensively during the last 15 years for developing a strategy in the field of MH information. Methods: The paper analyzes WHO instruments developed in this area [MH Atlas series and WHO Assessment Instrument for Mental Health Systems (WHO-AIMS)]. Results: Data from Atlas series and WHO-AIMS demonstrated that the role of information is often neglected at all the steps: from data collection and processing to analysis, dissemination and utilization, particularly in LAMIC. By implementing several sets of feasible MH indicators WHO has technically supported the improvement of the MH information systems in LAMICs. Conclusions: In the last few years the importance of information in MH has increased and has been successfully highlighted; but a lot of work still needs to be done for achieving a minimum set of MH indicators and reliable data that can be used by both high-income countries and LAMIC.